Digestion and absorption behaviors of goat milk fat from different lactation stages: an in-vitro comparative study - Zhang, Yan; Zheng, Zhaojun; Tan, Chin-ping; Liu, Yuanfa (Elsevier BV, 2024)
Goat milk is abundant in bioactive lipids that exhibit considerable variability across different lactation stages. This variability can potentially influence the bioavailability and overall nutrition benefits of goat milk for infants. In this study, we investigated the impact of lactation stages on the digestibility and absorbability of lipids in goat milk using an in vitro infant digestion model combined with an intestinal absorption model involving Caco-2 cells. In comparison to transitional and mature milk fats, goat colostrum fat exhibited the formation of smaller lipid aggregates during gastric digestion, despite their initial droplet sizes being similar. During gastrointestinal digestion, colostrum fat also released lower levels of free fatty acids (FFA, 47.49 % ± 1.01 %), specifically C6:0-C10:0, when compared to other milk fats. Furthermore, colostrum fat generated a small amount of monoacylglycerol (MAG, 16.11 % ± 0.95 %), mainly MAG 18:0, which differed from the predominant MAG 16:0 in transitional milk fat. Interestingly, incubation with colostrum fat induced the lowest triglyceride secretion in Caco-2 cells (243.54 ± 1.91 μmol/L). Conversely, treatment with transitional milk fat resulted in a higher number of intracellular lipid droplets, possibly due to the upregulation of genes such as DGAT1, DGAT2, PLIN2, and MTTP. In conclusion, our findings emphasize the persistent influence of lactation stages on the digestion and absorption properties of goat milk lipids. These insights offer valuable information for the precise utilization of goat milk in infant diets.